1986
DOI: 10.1111/j.1365-2133.1986.tb06646.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of altering area of application and dose per unit area on sensitization by DNCB

Abstract: We have investigated the contributions of dose per unit area and area of application to the degree of sensitivity induced by dinitrochlorobenzene (DNCB). Subjects sensitized with 35.4 micrograms/cm2 showed equal sensitization whether the total dose was 250 micrograms applied to 7.1 cm2 or 62.5 micrograms applied to 1.8 cm2. Three groups of subjects were sensitized with 16.4 micrograms/cm2 applied as 56 micrograms on 3.5 cm2, 116 micrograms on 7.1 cm2 or 232 micrograms on 14.2 cm2. Although the total dose chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 0 publications
1
37
0
1
Order By: Relevance
“…Several experimental investigations, especially with DNCB in human subjects, revealed that the induction of skin sensitization is dependent on the dose of the test chemical per skin area (Friedmann, 1990;White et al, 1986). Therefore, it has been widely recommended that sensitization thresholds obtained in LLNA, HRIPT or HMT should be expressed as the area dose (Boukhman and Maibach, 2001;Robinson et al, 2000;Roggeband et al, 2001).…”
Section: Parameter Explanationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental investigations, especially with DNCB in human subjects, revealed that the induction of skin sensitization is dependent on the dose of the test chemical per skin area (Friedmann, 1990;White et al, 1986). Therefore, it has been widely recommended that sensitization thresholds obtained in LLNA, HRIPT or HMT should be expressed as the area dose (Boukhman and Maibach, 2001;Robinson et al, 2000;Roggeband et al, 2001).…”
Section: Parameter Explanationmentioning
confidence: 99%
“…From research done during the last 15 years, e.g., using experimental human sensitization to 2,4-dinitrochlorobenzene (DNCB) (Friedmann et al, 1983;White et al, 1986;reviewed in Friedmann, 1990), we know today that skin sensitization as well as allergy elicitation only occur above threshold doses and follow predictable dose-response relationships (Basketter, 1998;Boukhman and Maibach, 2001;Kimber et al, 1999Kimber et al, , 2002Marzulli and Maibach, 1974;Roggeband et al, 2001;Scott et al, 2002;Van Och et al, 2001). It has become clear that skin sensitization is not different from other toxicological effects in this respect.…”
Section: Introductionmentioning
confidence: 96%
“…Using DNCB (dinitrochlorobenzene) as a model contact allergen, it was found that the dose per unit area of allergen was the critical parameter for whether sensitization occurred (27). The data demonstrated a threshold for the induction of clinically relevant sensitization to occur.…”
Section: Contact Sensitization: Observations On Exposurementioning
confidence: 99%
“…The assumption from this is that, in any given test system, an equal % exposure will lead to a similar incidence and/or severity of sensitization. However, in a series of elegant human skin sensitization studies, Friedmann and his colleagues proved that it is not the % (weight/volume) of material applied that is critical, but the total dose/area of exposed skin (11,26,(30)(31)(32)(33). They used a potent contact allergen, dinitrochlorobenzene (DNCB), and repeatedly exposed subjects to varying doses per unit area of skin to observe the incidence of sensitization upon challenge.…”
Section: Importance Of Dose/unit Area In the Skin Sensitization Processmentioning
confidence: 99%